2007
DOI: 10.1002/marc.200600626
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Highly Photoluminescent TiO2/PPV Hybrid Nanoparticle‐Polymer Fibers by Electrospinning

Abstract: In this study, we have synthesized highly photoluminescent TiO2/poly (phenylene vinylene) (PPV) hybrid nanoparticle‐polymer fibers by electrospinning a PPV precursor added to a TiO2 sol‐gel solution. The diameters of the hybrid fibers ranged from 100–300 nm and the average size of TiO2 nanoparticles within the fibers was 10–60 nm. FT‐IR analysis indicated that a new band around 1 632 cm−1 assigned to the TiOC vibration appeared, which resulted in the stronger luminance of the fluorescence of the TiO2/PPV hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…1b) at around 1450 cm -1 (Moradi et al 2012), and 1266 cm -1 (Jianjun et al 2001), corresponds to the Ti-O-C vibrations of the BC/TiO 2 , especially, the Ti-O network peak (at around 1008 cm -1 ) represents TiO 2 particles interacting with carbon of BC (Doeuff et al 1987). Moreover, the C=O vibration peak (1643 cm -1 ) of BC shifted downfield to the TiO 2 -OH vibration peak (1610 cm -1 ) of BC/TiO 2 (Wang et al 2007a;Zeng et al 2010). (Gutierrez et al 2012) found that the interaction of TiO 2 particles occurs at the interface of BC containing a large number of -OH (hydroxyl group) which forms hydrogen bonds.…”
Section: Resultsmentioning
confidence: 92%
“…1b) at around 1450 cm -1 (Moradi et al 2012), and 1266 cm -1 (Jianjun et al 2001), corresponds to the Ti-O-C vibrations of the BC/TiO 2 , especially, the Ti-O network peak (at around 1008 cm -1 ) represents TiO 2 particles interacting with carbon of BC (Doeuff et al 1987). Moreover, the C=O vibration peak (1643 cm -1 ) of BC shifted downfield to the TiO 2 -OH vibration peak (1610 cm -1 ) of BC/TiO 2 (Wang et al 2007a;Zeng et al 2010). (Gutierrez et al 2012) found that the interaction of TiO 2 particles occurs at the interface of BC containing a large number of -OH (hydroxyl group) which forms hydrogen bonds.…”
Section: Resultsmentioning
confidence: 92%
“…A drawback of PPV is its poor solubility and decomposition before melt, making it difficult to process and thus limiting its application. One strategy for solving this problem is to process the soluble sulfonium precursor of PPV, and then convert it into the conjugated form by a thermal elimination reaction, as reported by Xin et al [61][62][63]. In that work, the neutral polymer poly(vinyl pyrrolidone) (PVP) was introduced into PPV cationic polyelectrolyte precursor solution to increase the degree of bending instability during electrospinning.…”
Section: Poly(p-phenylene Vinylenes) (Ppvs)mentioning
confidence: 99%
“…As this jet travels, the solvent evaporates and an appropriate collector can be used to capture the polymer fiber. 14 Literature reports have focused on the improvement of the optoelectronic properties of conjugated polymers by combining them with semiconductor nanoparticles [15][16][17][18] or with clays. [19][20][21][22] However, to the authors' knowledge, there are no reports on clays of nanometer size in at least one of its dimensions that influences the phase separation of electrospun fibers based on blends of conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%